Proceedings of the 2020 International Conference on Multimodal Interaction 2020
DOI: 10.1145/3382507.3418844
|View full text |Cite
|
Sign up to set email alerts
|

Is She Truly Enjoying the Conversation?

Abstract: In human-agent interactions, it is necessary for the systems to identify the current emotional state of the user to adapt their dialogue strategies. Nevertheless, this task is challenging because the current emotional states are not always expressed in a natural setting and change dynamically. Recent accumulated evidence has indicated the usefulness of physiological modalities to realize emotion recognition. However, the contribution of the time series physiological signals in human-agent interaction during a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 30 publications
(33 reference statements)
0
0
0
Order By: Relevance
“…For example, in an emotion recognition task for spoken utterances, it was reported that the recognition performance based on machine learning was better on units to which multiple annotators gave the same labels (Seppi et al, 2008). As a preliminary investigation, we also calculated the mean square error of the sentiment estimation results as the regression from multimodal features (Katada et al, 2020) using 2,468 exchanges in Hazumi1911, where the references were the average of third-party sentiments. The correlation coefficient between the mean square errors and the standard deviations of the third-party sentiments per exchange was 0.342, which is statistically significant (p = 1.57×10 −68 ).…”
Section: Relationship Between Dispersion and Machine Learning Perform...mentioning
confidence: 99%
“…For example, in an emotion recognition task for spoken utterances, it was reported that the recognition performance based on machine learning was better on units to which multiple annotators gave the same labels (Seppi et al, 2008). As a preliminary investigation, we also calculated the mean square error of the sentiment estimation results as the regression from multimodal features (Katada et al, 2020) using 2,468 exchanges in Hazumi1911, where the references were the average of third-party sentiments. The correlation coefficient between the mean square errors and the standard deviations of the third-party sentiments per exchange was 0.342, which is statistically significant (p = 1.57×10 −68 ).…”
Section: Relationship Between Dispersion and Machine Learning Perform...mentioning
confidence: 99%